Sistem Informasi Pelayanan Praktik Mandiri Bidan Berbasis Website dengan Metode Waterfall : (Studi kasus: Bidan Tini di Desa Tanjung Bulan) - Apriansyah Apriansyah; Dheriessa Ayudhea; Jimmie Jimmie (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The Tini Midwife Independent Practice is a health institution that provides infant immunization, family planning services, and health check-ups. However, the patient administration process still uses conventional methods, namely notebooks, making it less effective and efficient. This study aims to design and implement a website-based service information system for the Tini Midwife Independent Practice to improve the process of administrative services. The system development method used is waterfall with Unified Modeling Language (UML) modeling. The programming language used is PHP with a MySQL database. This system makes it easier for midwives and administrators to record patient examination data, search for patient data and examination history, and create reports. In addition, patients can easily register for services and access diagnostic information and drug prescriptions through the website. The implementation of this system is expected to improve the effectiveness and efficiency of administrative services, reduce the risk of errors, streamline patient data management, and enhance service delivery. Ultimately, this system aims to provide better health service experiences for both staff and patients.